Studi Bahan Kemasan terhadap Viabilitas Benih Kedelai (Glycine max [L.] Merril) Pascasimpan Dua Belas Bulan di Ruang Simpan Suhu Rendah - Ermawati Ermawati; Niar Nurmauli; Paul Benjamin Timotiwu; Restu Deni Bimantara (Universitas Lampung, 2022)
Soybean is a commodity that is a source of vegetable protein that is easily obtained at a low price. The factor that affects low soybean productivity in Indonesia is the lack of use of quality seeds by farmers. Efforts to maintain the shelf life of soybean seeds can be done by using good packaging materials. The purpose of this study was to determine the effect of packaging materials that have different characteristics under low temperature storage conditions on the viability of soybean seeds after twelve months of storage. This research was carried out at the Seed and Plant Breeding Laboratory, Faculty, Agriculture, University of Lampung from October 2019 to June 2020. The treatment design was a single and unstructured factor, namely packaging material (b). The treatment of packaging materials consisted of aluminum foil (b1), polyethylene (b2), polypropylene (b3), brown envelope paper (b4), ordinary plastic (b5), calico fabric (b6). The packaging materials for six treatments were arranged in a randomized block design (RAK) with four replications. The results of this study showed that the viability of seeds was high in aluminum foil, polyethylene, polypropylene, ordinary plastic, envelope paper, and calico packaging materials in low temperature storage in an air-conditioned storage room after twelve months of storage. Twelve months post-stored seed viability was indicated by the germination rate of 87.48%; maximum growth potential of 96.25%; germination speed 30.96%; strong normal sprouts 81.19%; hypocotyl length 11.99 cm; dry weight of normal sprouts 31.82 mg; water content 7.30%; and electrical conductivity of 244.96 S/cm. Key words: viability, soybean seed, storage, packaging material, low temperature